Spin-sensitive interference due to Majorana state on the interface between normal and superconducting leads. (30th December 2016) - Barański, J; Kobiałka, A; Domański, T
Abstract: We investigate the subgap spectrum and transport properties of the quantum dot on the interface between the metallic and superconducting leads and additionally side-coupled to the edge of the topological superconducting (TS) chain, hosting the Majorana quasiparticle. Due to the chiral nature of the Majorana states only one spin component of the quantum dot electrons (say ↑ ) is directly affected, however the proximity induced on-dot pairing transmits its influence on the opposite spin as well. We investigate the unique interferometric patterns driven by the Majorana quasiparticle that are different for each spin component. We also address the spin-sensitive interplay with the Kondo effect manifested at the same zero-energy and we come to the conclusion that quantum interferometry can unambiguously identify the Majorana quasiparticle.